2022
DOI: 10.1371/journal.pone.0259951
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of hydropower planning in relation to the influence of climate in Northeast Brazil

Abstract: Water scarcity in Northeast Brazil has caused latent perturbations in hydropower generation, which is undesirable for Energy Planning. Thus, this study aims to identify the influence of climate on hydropower generation by Sobradinho Dam in Bahia by: (i) assessing the streamflow climatology (1964–2017) and rainfall (1964–2015) through time series analysis, hypothesis testing and cluster analysis; (ii) assessing hydropower generation (2000–2017) using climate and energy data, through principal component analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(39 reference statements)
2
0
0
3
Order By: Relevance
“…The findings of this study were found to be similar to the relationship between ONI and water level in Murum dam. The findings of this study were also found to have similarities with the findings of the study of Santos et al, (2022) found the occurrence of El Nino plays an important role in determining the water level in the Sobrahinho dam. Santos' study found that there was a relationship between the El Nino event and the water level in the Sobrahinho dam, Brazil with a negative test coefficient of 0.67 (P-value ˂ 0.05).…”
Section: Fig 9 -Correlation Relationship Between Oni and Water Level ...supporting
confidence: 84%
See 1 more Smart Citation
“…The findings of this study were found to be similar to the relationship between ONI and water level in Murum dam. The findings of this study were also found to have similarities with the findings of the study of Santos et al, (2022) found the occurrence of El Nino plays an important role in determining the water level in the Sobrahinho dam. Santos' study found that there was a relationship between the El Nino event and the water level in the Sobrahinho dam, Brazil with a negative test coefficient of 0.67 (P-value ˂ 0.05).…”
Section: Fig 9 -Correlation Relationship Between Oni and Water Level ...supporting
confidence: 84%
“…Figure 3 clearly shows the occurrence of ENSO through ONI has a significant impact on the amount of rainfall as per the findings of the study . The impact of this El Nino event is also not limited to Sarawak similar findings were also found in Brazil (Moura et al, 2019;Santos et al, 2022), in Ghana (Boadi & Uwusu, 2017), in China (Li et al al., 2021, Vietnam (Tham et al, 2022) and Indonesia (Irwandi et al, 2021).…”
Section: Resultssupporting
confidence: 68%
“…Estudos evidenciam tendência de aumento da severidade das secas, tendo como causa o aumento da evapotranspiração e a redução dos níveis de precipitação SUGG et al, 2020;IGLESIAS;TRAVIS;BALCH, 2022). Como consequências esperadas do fenômeno, podem ser citados insegurança e crises na produção de energia elétrica (HAYAT et al, 2018;SANTOS;LIMA;SPYRIDES, 2022); dificuldades na produção de alimentos (COTTREL et al, 2019); aumento no número de incêndios florestais (WHEILNHAMMER et al 2021); agravamento das condições de saúde física e psicológica humana (HAILE et al, 2020); diminuição e restrição de áreas disponíveis para a agricultura (KUWAYAMA et al, 2019) e impactos negativos na biodiversidade e serviços ecossistêmicos (ROUSTA et al, 2020;CARDOSO et al, 2022).…”
Section: Resultsunclassified
“…Como consequência, acredita-se que haverá um aumento significativo na frequência de eventos climáticos catastróficos, além de alterações ambientais que poderão resultar na redução das chuvas em diversas regiões e excesso em outras, impactando assim o meio ambiente e a sociedade. Por isso o conhecimento sobre o regime pluvial é de extrema importância, pois afeta na disponibilidade hídrica, no manejo da agricultura, na produção de energia, no abastecimento humano e animal, entre outros BEZERRA, 2018;LIMA, 2021;MEDEIROS et al, 2021;RODRIGUES et al, 2021;SIILVA et al, 2022;VALE et al, 2022;SANTOS et al, 2022).…”
Section: Introductionunclassified
“…De acordo com a Agência Nacional das Águas (ANA, 2012) estudos mais detalhados sobre os impactos das mudanças climáticas na América do Sul indicam que o Nordeste do Brasil (NEB) já apresenta um quadro de aumento da temperatura média do ar (CARVALHO et al, 2019;LUCENA, 2021;SANTOS et al, 2022) e tendências significativas nos índices de precipitação pluvial, especialmente na Bacia Hidrográfica do São Francisco (BEZERRA et al 2018;CARVALHO et al, 2019). Tendências em séries temporais das chuvas também têm sido analisadas no estado do Ceará (DA SILVA, 2016;HIERA et al, 2019), em Pernambuco (BEZERRA et al, 2021, no estado da Bahia (POUSA et al, 2019;SOUZA;NASCIMENTO, 2021), Rio Grande do Norte (CABRAL JÚNIOR; LUCENA, 2020), entre outros.…”
Section: Introductionunclassified